Biocomposite Polymer Embedded with Light-Sensitive Molecules for Plastic Displays - Hegde, Gurumurthy; A. R., Yuvaraj; Mei, Gan Siew; Siti Aisyah, Mustapha; M. M., Yusoff; V. G., Chigrinov (2014)
Achieving adhesion on plastic materials needs not only good photoaligning materials but also it needs lot of optimization in the production process. Here we are going to attempt to solve this problem by utilizing biocomposite mixture. Proposed method is cost effective and also easy to use.©(2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.